CP-217 Evaluation of efficacy, efficiency and persistence rate of biological therapy in the treatment of moderate to severe psoriasis in a third level reference hospital. (14th February 2016) - Calzado, G; Latour, I; Bullejos, M; Guimerá, FJ; Vázquez, C; Nazco, J
Abstract : Background: Hospital pharmacy management is responsible for procurement, medication order review and dispensing of drugs for the treatment of psoriasis. Low persistence is one of the main reasons for increased costs but to date there has not been enough evidence. This is necessary information for clinical practice. Purpose: To estimate the persistence rate, long term efficacy and efficiency of biological treatments etanercept, adalimumab and ustekinumab in the treatment of moderate to severe psoriasis. Material and methods: An observational, retrospective study from a single centre. It was carried out from April 2012 to October 2015 in all naive patients who started treatment with etanercept, adalimumab or ustekinumab for moderate to severe psoriasis, for at least 24 weeks. Drug persistence was analysed by the Kaplan-Meier method with the log rank test. We evaluated efficiency by cost effectiveness. Efficacy was estimated using risk difference of the Psoriasis Area and Severity Index (PASI) 75 response rates at the endpoint (week 12 for etanercept and ustekinumab, and week 16 for adalimumab), at the end of the induction phase (week 24) and at the time points recommended for evaluation of primary failure in the approved summaries of product characteristics. Results: We analysed 98 patients (50% men), mean age 46 (22–80) years. Etanercept (40 patients), adalimumab (35 patients) or ustekinumab (23 patients) were used as treatments. Mean PASI at baseline was 10.8 (3.7–23.3). 18 patients discontinued treatment due to side effects, pregnancy or primary failure. Persistence rate results: 82.5% etanercept, 77.1% adalimumab and 87% ustekinumab. Regarding efficacy, at the primary endpoint, ustekinumab was the most effective drug (95.7%), followed by adalimumab (79.4%) and etanercept (60.5%). At the end of the induction phase, ustekinumab had the greatest probability of response (95.7%) in comparison with adalimumab (78.8%) and etanercept (68.6%). At the time points recommended for primary failure, ustekinumab was also the most effective drug.  Conclusion: According to our clinical practice perspective, ustekinumab was the most effective drug in naive patients during all studied periods. Furthermore, it was supported by persistence rate. No conflict of interest.